Amino Acid Uptake Measured by [(18)F]AFETP Increases in Response to Arginine Starvation in ASS1-Deficient Sarcomas - Prudner, Bethany Cheree (Theranostics, 2018)
Rational: In a subset of cancers, arginine auxotrophy occurs due to the loss of expression of argininosuccinate synthetase 1 (ASS1). This loss of ASS1 expression makes cancers sensitive to arginine starvation that is induced by PEGylated arginine deiminase (ADI-PEG20). Although ADI-PEG20 treatment is effective, it does have important limitations. Arginine starvation is only beneficial in patients with cancers that are ASS1-deficient. Also, these tumors may metabolically reprogram to express ASS1, transforming them from an auxotrophic phenotype to a prototrophic phenotype and thus rendering ADI-PEG20 ineffective. Due to these limitations of ADI-PEG20 treatment and the potential for developing resistance, non-invasive tools to monitor sensitivity to arginine starvation are needed. Methods: Within this study, we assess the utility of a novel positron emission tomography (PET) tracer to determine sarcomas reliant on extracellular arginine for survival by measuring changes in amino acid transport in arginine auxotrophic sarcoma cells treated with ADI-PEG20. The uptake of the (18)F-labeled histidine analogue, (S)-2-amino-3-[1-(2-[(18)F]fluoroethyl)-1H-[1,2,3]triazol-4-yl]propanoic acid (AFETP), was assessed in vitro and in vivo using human-derived sarcoma cell lines. In addition, we examined the expression and localization of cationic amino acid transporters in response to arginine starvation with ADI-PEG20. Results: In vitro studies revealed that in response to ADI-PEG20 treatment, arginine auxotrophs increase the uptake of L-[(3)H]arginine and [(18)F]AFETP due to an increase in the expression and localization to the plasma membrane of the cationic amino acid transporter CAT-1. Furthermore, in vivo PET imaging studies in mice with arginine-dependent osteosarcoma xenografts showed increased [(18)F]AFETP uptake in tumors 4 days after ADI-PEG20 treatment compared to baseline. Conclusion: CAT-1 transporters localizes to the plasma membrane as a result of arginine starvation with ADI-PEG20 in ASS1-deficient tumor cells and provides a mechanism for using cationic amino acid transport substrates such as [(18)F]AFETP for identifying tumors susceptible to ADI-PEG20 treatment though non-invasive PET imaging techniques. These findings indicate that [(18)F]AFETP-PET may be suitable for the early detection of tumor response to arginine depletion due to ADI-PEG20 treatment.